A remark on Schottky representations and Reidemeister torsion - Hezenci, F.; Sozen, Y. (Bulletin of the Karaganda University. Mathematics Series, 2023)
The present paper establishes a formula of Reidemeister torsion for Schottky representations. The theoretical results are applied to 3-manifolds with boundary consisting orientable surfaces with genus at least 2.